Proving participation: vocational bureaucrats and bureaucratic creativity in the implementation of the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage. (17th February 2020) - Bortolotto, Chiara; Demgenski, Philipp; Karampampas, Panas; Toji, Simone
Abstract : This paper investigates the bureaucratisation of the (utopian) ideal of community participation in Intangible Cultural Heritage (ICH) safeguarding and management. The analysis considers the whole 'policy life' of the UNESCO Convention for the Safeguarding of ICH. Our ethnographic examples from UNESCO, Brazil, China and Greece illustrate how bureaucratic operations often disenchant the participatory ideal, alienating it from its original intention. At the same time, driven by their commitment to 'good' governance and informed by sentiments of frustration and disappointment with actual policy results, vocational bureaucrats at different administrative levels experiment with and conceive of new tools in order to produce evidence of participation. We demonstrate how this bureaucratic creativity has concrete consequences, which may differ from the intended utopia, but nevertheless bring to life particular interpretations of the participatory principle among the recipients for whom heritage policies were originally designed. Thus, we present a more nuanced picture of bureaucratisation in which officials' emotions and engagement sustain their agency against structural constraints as well as the futility and fragility of administrative procedures. Démontrer la participation: la place des bureaucrates vocationnels et de la créativité bureaucratique dans la mise en œuvre de la Convention de l'UNESCO pour la sauvegarde du patrimoine culturel immatériel: Cet article examine la bureaucratisation de l'idéal (utopique) de participation de la communauté dans la sauvegarde et la gestion du patrimoine culturel immatériel (PCI). L'analyse se penche sur l'ensemble de la « vie administrative » de la Convention de l'UNESCO pour la sauvegarde du PCI. Nos exemples ethnographiques – qui viennent de l'UNESCO, du Brésil, de la Chine et de la Grèce – montrent à quel point les opérations bureaucratiques désenchantent souvent l'idéal participatif, en le détournant de ses intentions premières. Parallèlement, motivés par leur engagement pour une « bonne » gouvernance et poussés par un sentiment de frustration et de déception devant les résultats réels de ce modèle, des bureaucrates vocationnels, à des niveaux administratifs divers, conçoivent et expérimentent de nouveaux outils dans le but de produire des preuves de cette participation. Nous démontrons que cette créativité bureaucratique a des conséquences concrètes, parfois éloignées du projet utopique de départ, mais qui donnent cependant lieu à des interprétations singulières du principe de participation parmi ceux pour qui les politiques patrimoniales étaient initialement conçues. Ainsi, nous dressons un tableau plus nuancé de la bureaucratisation, dans lequel l'engagement et les émotions des responsables alimentent leur action en dépit des contraintes structurelles, de la futilité et de la fragilité des procédures administratives.